Idiopathic Scrotal Hematoma in Neonate: A Case Report and Review of the Literature - Bioku Muftau Jimoh; Eziechila Bessie Chinwe; Adewumi Oluwafemi Adebisi; Igwilo Chinwe Ifeoma; Maduka Ogechi; Aiyekomogbon Joshua Oluwafemi (Case Reports in Urology)
Neonatal scrotal hematoma is a rare genitourinary emergency. Some cases have underlining aetiologic factors such as testicular torsion, adrenal hemorrhage, or birth trauma, and others are idiopathic. Previously, immediate scrotal exploration was considered imperative for diagnosis and treatment. With good imaging techniques, some patients are managed nonoperatively. We report a case of idiopathic scrotal hematoma in a neonate. He was managed conservatively with clinical and radiological follow-up. There was complete resolution of hematoma within two months, thus, avoiding unnecessary exploration.